Lean in a Changed World. (Manufacturing Engineering)
After 20 years, less than 10 percent of the companies that have initiated lean are exploiting it fully. A breakthrough is needed to reach the hundreds of thousands of North American organizations that are ignoring the huge gains that system wide leverage can bring.